Yield design-based analysis of high rise concrete walls subjected to fire loading conditions. (15th March 2015) - Pham, Duc Toan; de Buhan, Patrick; Florence, Céline; Heck, Jean-Vivien; Nguyen, Hong Hai
Highlights: The stability of a high rise wall in fire is analyzed in its deformed configuration. The method proposed is particularly well suited for a preliminary engineering design. A first investigation shows that wall failure is highly sensitive to its height. Abstract: Relying on a simplified one dimensional beam-like schematization of the problem, a yield design-based approach is developed for analyzing the potential failure of high rise walls (that are larger than the dimensions of experimental test furnaces) under fire conditions. The implementation of the method combines two original features: first, the preliminary determination of interaction diagrams reflecting the local decrease in strength of the wall due to thermal loading; second, the thermal-induced geometry changes which are explicitly accounted for in the overall failure design of the wall. Application of the approach is illustrated in either evaluating the fire resistance of a wall of given height or predicting the maximum height that the wall could reach for a prescribed fire exposure time. First results of this analysis point to the conclusion that wall failure due to fire loading is highly sensitive to its height.